ChatGPT: Keuntungan, Risiko, Dan Penggunaan Bijak Dalam Era Kecerdasan Buatan - Misnawati Misnawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This article discusses the benefits, risks, and wise use of Artificial Intelligence (AI) technology, with a focus on ChatGPT, a large language model. AI technology has become an integral part of modern human life, with various applications in industries such as business, health, government, and others. AI technology can help improve decision-making based on data, reduce human error, and increase efficiency. However, it also poses risks, such as data security and job replacement. To ensure the wise use of AI, it is crucial to observe AI ethics, protect user data and privacy, avoid discrimination, and ensure system security. The research problem is formulated to answer questions such as the benefits and risks of using ChatGPT, its optimal use, and its role in education. The purpose of the research is to describe the benefits, risks, and wise use of ChatGPT in the era of AI and to ensure its responsible use.